2019
DOI: 10.1002/dac.4150
|View full text |Cite
|
Sign up to set email alerts
|

Odd clipping optical orthogonal frequency division multiplexing for VLC system

Abstract: The Orthogonal Frequency Division Multiplexing (OFDM) has emerged as one of the promising techniques because of its robustness to multipath fading with high-speed data transmission. Classical bipolar OFDM cannot be used in intensity modulated with direct detection (IM/DD) optical communication systems, as visible light communication (VLC), so many optical modulation techniques as asymmetrical clipped optical OFDM (ACO-OFDM) and DC-Clipped OFDM (DCO-OFDM) have been investigated. In this paper, we introduce a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Many types of research over the past decade addressed this challenge and introduced the unipolar OFDM schemes. Several optical OFDM techniques have been developed as the direct current (DC) biased optical OFDM (DCO-OFDM) [8] [10], the asymmetrically clipped optical OFDM (ACO-OFDM) [9] [10].…”
Section: Fig 3 Oqam-fbmc Transmittermentioning
confidence: 99%
See 1 more Smart Citation
“…Many types of research over the past decade addressed this challenge and introduced the unipolar OFDM schemes. Several optical OFDM techniques have been developed as the direct current (DC) biased optical OFDM (DCO-OFDM) [8] [10], the asymmetrically clipped optical OFDM (ACO-OFDM) [9] [10].…”
Section: Fig 3 Oqam-fbmc Transmittermentioning
confidence: 99%
“…On the other hand, the ACO schemes are based on utilizing only the odd subcarriers and adding zeros on the even subcarriers. It has been shown that even subcarriers carry the clipping distortion [8]. The ACO-OFDM has high power efficiency and low spectral efficiency as only the odd subcarriers carry the data.…”
Section: Fig 3 Oqam-fbmc Transmittermentioning
confidence: 99%
“…In OCO-OFDM technique shown in Fig. 2 (b), a real unipolar signal is produced by applying odd symmetry on the frequency domain OFDM frame before the IFFT operation [8]. The odd symmetry requires that:…”
Section: B Optical Ofdm Modulation and Multiple Accessmentioning
confidence: 99%
“…Orthogonal frequency division multiplexing (OFDM) has been proposed as the most spectrally efficient technique that provides a high data rate and significantly improves the system capacity due to its robustness to the multipath fading [5]. A VLC system using a white LED as a communication source requires a real unipolar signal, so optical OFDM techniques have been introduced as asymmetrically clipped optical OFDM (ACO-OFDM), DC-biased optical OFDM (DCO-OFDM) [6], asymmetrically clipped DC-biased optical OFDM (ADO-OFDM) [7] and odd clipped optical OFDM (OCO-OFDM) [8]. In DCO-OFDM, Hermitian symmetry is imposed on all the subcarriers that carry the data, which produces a real bipolar signal, then DC offset is added to get the unipolar signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conventional OFDM signal based on the Fourier Transform (FT) cannot be considered an effective solution for optical wireless communication because it does not meet the real and positive signal requirements. Modified variations of the conventional OFDM technique have been introduced to generate real and positive signals such as the asymmetrical clipped optical OFDM (ACO-OFDM), the dc-clipped optical OFDM (DCO-OFDM), and the odd-clipped optical OFDM (OCO-OFDM) [4] [5]. ACO-OFDM and DCO-OFDM are applying Hermitian symmetry to optical carriers to generate a real OFDM signal.…”
Section: Introductionmentioning
confidence: 99%